1976
DOI: 10.1073/pnas.73.3.767
|View full text |Cite
|
Sign up to set email alerts
|

Lack of ribosomal protein S1 in Bacillus stearothermophilus.

Abstract: The 30S ribosomal subunit of Bacillus stearothermophilus migrated as a single band when electrophoresed on agarose-acrylamide composite gels. The addition of the ribosomal protein SI purified from Escherichia coli resulted in the appearance of an additional band migrating more slowly; "Clabeled SI of E. coli was shown to be associated only with this form. Antibody against E. coli protein SI did not crossreact with either the total 30S ribosomal proteins or the postribosomal supernatant from B. stearothermophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…31) Inactivation of ypfD, which encodes the S1 homologue in B. subtilis, 32) also caused a considerable decrease in sporulation at high temperature (Table 3). Sorokin et al 33) reported previously that ypfD (designated it as the gene jofD) is expressed but is not essential in B. subtilis.…”
Section: Discussionmentioning
confidence: 99%
“…31) Inactivation of ypfD, which encodes the S1 homologue in B. subtilis, 32) also caused a considerable decrease in sporulation at high temperature (Table 3). Sorokin et al 33) reported previously that ypfD (designated it as the gene jofD) is expressed but is not essential in B. subtilis.…”
Section: Discussionmentioning
confidence: 99%
“…ribosomes is the apparent lack of a counterpart to the S1 ribosomal protein of Gram-negative bacteria (Higo et al, 1973(Higo et al, , 1982Isono & Isono, 1975;Schnier & Faist, 1985;Muralikrishna & Suryanarayana, 1985 ;Roberts & Rabinowitz, 1989 ; Farwell e t al., 1992). In Gram-negatives initiation of translation is facilitated by two components, one of which is a purine-rich sequence of mRNA, called the Shine-Dalgarno (SD) sequence, appropriately spaced from an initiation codon, and the second is the ribosomal protein S1, which has been shown to bind mRNA thus facilitating recognition of the initiation point (Roberts & Rabinowitz, 1989;Farwell et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The AG's of the ribosome-binding sites for the dnaE and rpoD genes (the second and third genes of the operon) are -13.8 (30) (31) make this explanation unlikely. On the other hand, the absence of ribosomal protein Si in B. subtilis (9) and the recent discovery of the differences between B. subtilis and E. coli in two important ribosomal protein-containing operons, i.e., the rpoD (3,15,28,29) and rpoA operons (10,26), suggest a possible difference in the ribosome components and functions that might explain the different expression patterns of the same genes as observed in our studies:…”
Section: Methodsmentioning
confidence: 43%